2012
DOI: 10.3325/cmj.2012.53.162
|View full text |Cite
|
Sign up to set email alerts
|

On-admission serum uric acid predicts outcomes after acute myocardial infarction: systematic review and meta-analysis of prognostic studies

Abstract: AimTo evaluate the prognostic value of serum uric acid (SUA) in acute myocardial infarction (AMI) patients.MethodsSystematic review and random-effects meta-analysis of prognostic studies assessing AMI outcomes (death, major adverse cardiac events, MACE) in relation to on-admission SUA.ResultsNine studies (7655 patients) were identified, 6 in the ST-segment elevation AMI patients treated with invasive revascularization and three in mixed AMI type cohorts with variable reperfusion strategies. “High” SUA (vs “low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Kaya et al showed that a high UA level on admission was independently associated with MACE in patients with ST-elevation myocardial infarction who undergo PCI [17]. The meta-analysis by Trkulja et al reported a significant association between UA level and short-and long-term outcomes after acute myocardial infarction [24]. Some studies have demonstrated that there is a significant relationship between UA level and post-primary PCI myocardial perfusion grade [22,25].…”
Section: Ua and Cardiovascular Eventsmentioning
confidence: 92%
“…Kaya et al showed that a high UA level on admission was independently associated with MACE in patients with ST-elevation myocardial infarction who undergo PCI [17]. The meta-analysis by Trkulja et al reported a significant association between UA level and short-and long-term outcomes after acute myocardial infarction [24]. Some studies have demonstrated that there is a significant relationship between UA level and post-primary PCI myocardial perfusion grade [22,25].…”
Section: Ua and Cardiovascular Eventsmentioning
confidence: 92%
“…[2][3][4] Furthermore, UA was found to be a strong marker of cardiovascular disease including acute and chronic heart disease, heart failure and stroke. [5][6][7][8] Acute myocardial infarction (AMI) remains one of the most significant causes of death worldwide, and patients with AMI have a higher mortality rate during the first month following an event, especially during in-hospital stays. [9] Hence, in this study, we aimed to evaluate the relationship between serum UA levels and cardiovascular events and the incidence of mortality during in-hospital period in patients with STelevated acute myocardial infarction (STEMI).…”
Section: P Revious Studies Havementioning
confidence: 99%
“…Similar studies conducted in Croatia by Vladimir Trkulj et al 16 and Ersan Tatli et al 17 concluded that high serum uric acid at admission independently predicts worse short-term and medium/long-term outcomes after AMI, poor outcomes in MACE and associated with higher in-hospital mortality and thirty-day mortality and poor long-term survival after AMI.…”
Section: Resultsmentioning
confidence: 52%